23rd Joint Propulsion Conference 1987
DOI: 10.2514/6.1987-2120
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary performance characterizations of an engineering model multipropellant resistojet for space station application

Abstract: SUMMARYlhis paper presents the results of a program to describe the operational characteristics of an engineering model multipropellant resistojet for application as an auxiliary propulsion system for space station. Performance was measured on hydrogen, helium, methane, water (steam), nitrogen, air, argon, and carbon dioxide. Thrust levels ranged from 109 to 355 mN, power levels ranged 2 from 167 to 506 W , and specific impulse values ranged from 93 to 385 sec, depending upon the propellant, chamber pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…The cold gas specific impulse for the hydrogen resistojet is approximately 380 sec at a power level of 329 W. In comparison, the cold gas hydrogen performance (with no heater power) is 250 sec (Ref. 35). …”
Section: S Resistojet Researchmentioning
confidence: 96%
“…The cold gas specific impulse for the hydrogen resistojet is approximately 380 sec at a power level of 329 W. In comparison, the cold gas hydrogen performance (with no heater power) is 250 sec (Ref. 35). …”
Section: S Resistojet Researchmentioning
confidence: 96%
“…5. 12 The average molecular weight of the gases produced from the steam reforming is 36.3 gm/mole, resulting in a resistojet specific impulse of 134.3 sec and a coldgas specific impulse of 64.4 sec. If secondary reactors are included to take the waste processing all the way to oxygen and methane, the mass ratio produced is approximately 1.5 to 1.…”
Section: B Performance Potentialmentioning
confidence: 99%
“…The TtG system could be tailored to maximize recovery of water from the waste, or produce other gasses depending on the application. In addition to methane propolusion, gasses produced from the oxidation of waste, such as carbon dioxide and carbon monoxide, can be used for resistojet propulsion 2 . TtG technologies will process all combustible waste, including human metabolic waste, thereby reducing the volume of waste that needs to be stored, and stabilizing the waste, minimizing the possibility of unwanted microbial activity on a spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…(1) (2) Previous studies have investigated incineration and gasification for processing of spaceflight waste. 4 ' 5 These studies demonstrated feasibility of the process and identified critical reaction parameters for different waste materials.…”
Section: Introductionmentioning
confidence: 99%